Perbandingan Kinerja RouterOS Mikrotik dan Zeroshell pada Mekanisme Load Balancing Serta Failover - Ardy Frayogi; Widhi Yahya; Raden Arief Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The Internet becomes an important need in society. The problem that is often faced by the public to access the internet is a slow connection and unstable internet service provider. Multiconnection is one solution that can be used to make access to the Internet network for better. Multiconnnection requires a technique called load balancing and failover. It is used to maximize throughput so that access to the internet becomes more stable and faster. Implementing load balancing and failover requires routerOS to be able to control incoming packets. RouterOS that features load balancing and failover are Mikrotik and Zeroshell. In this study will apply and compare the performance of load balancing and failover that is applied to router Mikrotik and Zeroshell. The load balancing method used in Mikrotik is nth and in Zeroshell uses round-robin method. Based on the results of the study concluded both routerOS can run very well with load balancing and failover. The result of load balancing performance applied to MikroTik using nth method has higher throughput value compared to the throughput value applied to Zeroshell load balancing. Performance results on failover tests applied to Mikrotik have a smaller delay value compared to the failover test applied to Zeroshell.